Distribusi Bahan Organik pada Sedimen Permukaan Teluk Kelabat, Pulau Bangka - Mohammad Agung Nugraha; Mu’alimah Hudatwi (Universitas Diponegoro, 2020)
Transport of organic material in coastal areas plays an important role in the global biogeochemical cycle. The purpose of this study was to examine the distribution of organic material in sediments and to identify sources of organic material in the Kelabat Bay waters. TOC and TN sediments were analyzed by the Walkley Black and Kjeldahl method. The value of TOC, TN, and C/N ratio obtained in the Kelabat Bay waters sediments ranged from 0.04-7.25%, 0.04-0.14%, and 0.67-65.91. The distribution of TOC, TN, and C/N ratio in Kelabat Bay sediments shows that the value in the inner Kelabat Bay is higher than the outside. The source of organic material input in the inner Kelabat Bay comes mainly from terrestrial, while the outer Kelabat Bay mainly comes from aquatic. Transport bahan organik pada wilayah pesisir memainkan peran penting dalam siklus biogeokimia secara global. Tujuan penelitian ini untuk mengkaji distribusi bahan organik pada sedimen serta identifikasi sumber bahan organik perairan Teluk Kelabat. TOC dan TN sedimen dianalisis dengan metode Walkley Black dan Kjeldahl. Nilai TOC, TN, dan rasio C/N yang diperoleh pada sedimen perairan Teluk Kelabat berkisar antara 0,04-7,25%, 0,04-0,14%, dan 0,67-65,91. Distribusi TOC, TN, serta rasio C/N pada sedimen Teluk Kelabat memperlihatkan nilai pada Teluk Kelabat bagian dalam lebih tinggi dibandingkan bagian luar. Sumber masukan bahan organik pada Teluk Kelabat bagian dalam utamanya berasal dari terestrial, sedangkan Teluk Kelabat bagian luar utamanya berasal dari akuatik.